Field-induced energy band and effective mass anisotropy in coupled double quantum wells - Velásquez, R.; Pankiewicz, C. G. (Superlattices and Microstructures, 2008)
The effects of the field-induced conduction band anisotropy on the electron effective mass and electrical transport properties of coupled double quantum well structures are discussed. This anisotropy is due to the formation of a partial energy gap in the dispersion curves of coupled double quantum wells by an in-plane magnetic field. The reported data show that the magnitude of this gap is mainly dependent on the interwell coupling, although it also depends on the magnitude of the applied magnetic field. A field-induced anisotropy of the electron effective mass and the in-plane electrical transport properties, due to the formation of a saddle point at the lower edge of this gap, is predicted. Further, a simple model to estimate the critical field at which a saddle point appears is also discussed.
Keywords: Magnetotunneling spectroscopy; Effective mass; Quantum wells